1994
DOI: 10.1007/bf03010933
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular effects of vecuronium and neostigmine in Montreal and Paris

Abstract: The potency of vecuronium was reported to be greater in Montreal than (28,5 5:6,8 In 1969, Katz et al. ~ reported that the maximum blockade attained after a single dose of d-tubocurarine or sueeinylcholine was greater and the duration of action was longer in New York than in London. The study was performed before dose-response techniques became common practice in the evaluation of muscle relaxants, and before a standard mode of stimulation, the train-of-four, 2 was introduced into clinical use and researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It was suggested that the 30-40% transatlantic difference in potency and duration of action of vecuronium was most likely due to differences in protein binding or sensitivity of the neuromuscular junction. 19 The lack of difference in time course of mivacufium suggests that there were no details of monitoring, anaesthetic administration or epidemiological factors affecting plasma cholinesterase activity which differed between Pittsburgh and Helsinki.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the 30-40% transatlantic difference in potency and duration of action of vecuronium was most likely due to differences in protein binding or sensitivity of the neuromuscular junction. 19 The lack of difference in time course of mivacufium suggests that there were no details of monitoring, anaesthetic administration or epidemiological factors affecting plasma cholinesterase activity which differed between Pittsburgh and Helsinki.…”
Section: Discussionmentioning
confidence: 99%